Sexual activity and dyspareunia the first year postpartum in relation to degree of perineal trauma. Issue 10 (October 2016) - Fodstad, Kathrine; Staff, Anne; Laine, Katariina
Abstract Introduction and hypothesis Knowledge on sexual complaints and time to sexual resumption after obstetric anal sphincter injury (OASI) is scarce. The aim of the study was to investigate self-reported sexual activity and coital problems 1 year postpartum in relation to perineal trauma, in addition to delivery mode. Methods Among 2, 846 women recruited during pregnancy, all women who delivered with OASI (n  = 42, all third-degree perineal tears), in addition to 20 randomly selected controls per OASI case, a total of 882 women, were sent a self-administered questionnaire addressing time to coital resumption after delivery and potential coital difficulty 1 year postpartum. Results By 8 weeks, half of the 561 responders (51.4 %) had resumed intercourse, increasing to 75.2 % by 12 weeks and 94.7 % 1 year postpartum. In multivariate regression analysis OASI was the strongest predictor for postponed coital onset, defined as after 8 weeks (aOR 5.52, CI 1.59–19.16). OASI was also the only significant predictor for dyspareunia 1 year after delivery (aOR 3.57, CI 1.39–9.19). Episiotomy was neither a risk factor for postponed coital onset nor for dyspareunia. There were no differences between episiotomy and second-degree laceration injury groups regarding postponed coital onset (p  = 0.45) or dyspareunia (p  = 0.67) 1 year postpartum. Conclusions Obstetric anal sphincter injury was a strong and independent predictor for both postponed coital resumption after delivery and for dyspareunia 1 year postpartum, whereas episiotomy and spontaneous second-degree lacerations were not. Our main finding of affected sexual activity after OASI further supports the need to reduce the rates of this obstetric injury to a minimum.